2014
DOI: 10.1159/000360225
|View full text |Cite
|
Sign up to set email alerts
|

Non-Axial View of the Varicella-Zoster Virus Portal Protein Reveals Conserved Crown, Wing and Clip Architecture

Abstract: Background: Herpesviridae encode a family of protein homologues that function as the ‘port of entry' for insertion of the viral DNA into preformed capsids during encapsidation. Methods: Transmission electron microscopy (TEM) of recombinant varicella-zoster virus pORF54 was performed. Results: Results suggest that pORF54 forms higher-order structures with itself. Enriched fractions analyzed by TEM revealed non-axial oriented portals with defined central channels and distinguishable crown, wing and clip regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Studies by Newcomb et al showed that pUL6 assembled into ring-like structures in vitro that form a portal of entry for viral DNA into the capsid (15). VZV pORF54 shows 44% amino acid identity with its HSV-1 pUL6 homolog (18,77), and it recently was shown to form portallike structures when expressed in insect cells (18,19). The results reported in this paper suggest that pORF54 performs a functional role similar to that of pUL6 during VZV replication.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Studies by Newcomb et al showed that pUL6 assembled into ring-like structures in vitro that form a portal of entry for viral DNA into the capsid (15). VZV pORF54 shows 44% amino acid identity with its HSV-1 pUL6 homolog (18,77), and it recently was shown to form portallike structures when expressed in insect cells (18,19). The results reported in this paper suggest that pORF54 performs a functional role similar to that of pUL6 during VZV replication.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies provided evidence that HSV-1 pUL6 forms the portal protein through which DNA can enter the viral procapsid (8,(14)(15)(16)(17). Subsequently, we showed that ORF54 encodes the homologous portal protein for VZV, pORF54 (18,19). Small molecules that target the HSV (20) and VZV (21) portal proteins have been described.…”
mentioning
confidence: 89%
“…HSV‐2 pUL6 is encoded by the 2034‐bp UL6 gene. Although pUL6‐2 contains 2 additional aa residues compared with HSV‐1 (Table ), pUL6‐1 and ‐2 share >85% aa sequence identity (Figure ) and therefore are likely to be similar in structure and function . Thiourea compounds showed only modest activity against HSV‐2 strains (Table ) .…”
Section: Herpes Simplex Virus Typementioning
confidence: 99%
“…pORF54 was shown to be the structural and functional homolog of HSV‐1 pUL6. pORF54 expressed in a recombinant baculovirus system formed oligomeric VZV portals containing the typical crown‐wing‐stem‐clip portal architecture observed in phage portals (Figure A). VZV ORF54 mutants created via recombineering were only viable in a complementing pORF54‐expressing cell line .…”
Section: Varicella‐zoster Virusmentioning
confidence: 99%
See 1 more Smart Citation